Mechanisms Involved in A2E Oxidation - Kim, So Ra (2008)
A2E is one of the bis-retinoid pyridinium compounds that accumulate as lipofuscin pigments in retinal pigment epithelial (RPE) cells in association with aging and in some inherited forms of retinal degeneration. Here we observed that 430 nm irradiation of A2E in the presence of the spin trap DMPO, led to the appearance of a superoxide dismutase-inhibitable electron paramagnetic resonance (EPR) spectrum characteristic of DMPO-OH; this finding was indicative of hydroxyl radical (OH) formation following initial spin trapping of superoxide anion by DMPO. We also observed an increase in dihydroethidium (HEt) fluorescence and luminol-based chemiluminescence that on the basis of inhibition by superoxide dismutase, was indicative of superoxide anion generation when A2E was irradiated at 430 nm in cell-free systems. Nevertheless, while A2E was readily oxidized in the presence of a singlet oxygen generator, superoxide anion did not serve to oxidize A2E. Specifically, by HPLC quantitation and FAB-mass spectroscopy, there was no evidence of A2E oxidation when A2E was incubated with a superoxide anion generator (xanthine/xanthine oxidase) in a variety of solvents (100% PBS, 30% DMSO in PBS, 100% MeOH and CHCl(3)) or in the presence of detergent. On the other hand, however, peroxy-A2E, an oxidized form of A2E with an endoperoxide moiety on the short-arm of the molecule, readily underwent further oxygen addition when incubated with xanthine/xanthine oxidase. Superoxide anion may be generated by irradiation of A2E but is not involved in the early events that oxidize A2E. Superoxide can contribute to the further oxidation of already-oxidized A2E.